A research on the effect of the country image on memorable tourism experience in the context of some demographic variables - Kutlu, Didem; Ayyildiz, Hasan (Anais Brasileiros de Estudos Turísticos, 2023)
With the world economy developing based on experience, businesses are trying to create unique experiences to differentiate themselves. The transformation of these experiences into a memorable tourism experience (MTE) not only affects customer satisfaction, but also positively affects the country image which is the impression of consumers about the country. Therefore, this study intents to find the effect of country image on MTE and to reveal which dimensions of country image affect the MTE. Moreover, the effect of demographic factors on the perception of the country image will be investigated. The study was carried out with 707 international tourists visited Antalya, a well-known destination in Turkey, during the months of May-October in 2018. As a result of hierarchical regression analysis the effect of country image on MTE was partially supported and it was revealed that MTE had a positive effect on hedonism, novelty, local culture, and meaningfulness dimensions. Regarding the second objective, a significant difference was found between the marital status, age groups and educational status of international tourists and their country image perceptions. Due to the impact of country image on MTE, policy makers need to make continuous improvement in the context of political, technological, and environmental factors.